Electron spin density on the axial His ligand of high-spin and low-spin Nitrophorin 2 probed by heteronuclear NMR spectroscopy - Abriata, Luciano A. (2013)
The electronic structure of heme proteins is exquisitely tuned by the interaction of the iron center with the axial ligands. NMR studies of paramagnetic heme systems have been focused on the heme signals, but signals from the axial ligands have been rather difficult to detect and assign. We report an extensive assignment of the (1)H, (13)C and (15)N resonances of the axial His ligand in the NO-carrying protein nitrophorin 2 (NP2) in the paramagnetic high-spin and low-spin forms, as well as in the diamagnetic NO complex. We find that the high-spin protein has σ spin delocalization to all atoms in the axial His57, which decreases in size as the number of bonds between Fe(III) and the atom in question increase, except that within the His57 imidazole ring the contact shifts are a balance between positive σ and negative π contributions. In contrast, the low-spin protein has π spin delocalization to all atoms of the imidazole ring. Our strategy, adequately combined with a selective residue labeling scheme, represents a straightforward characterization of the electron spin density in heme axial ligands.